ANALYSIS OF NORMS OF LAW IN NORMATIVE ACTS REGULATING RELATIONS IN THE FIELD OF FOREST LEGISLATION AND IN THE FEDERAL LAW NO. 294-FZ OF DECEMBER 26, 2008 - Shegelman I. R., Kornilov K. A. (A breakthrough in science: development strategies, 2018)
contradictions in the norms of law contained in legal acts regulating relations in the field of forest legislation are noted, and in Federal Law No. 294-FZ of December 26, 2008.
Keywords: нормы права; лесное законодательство; forest legislation; лесные отношения; forest relations; rules of law